Perancangan mesin pencetak bantalan palet dari serbuk kayu - Riki Effendi; Franka Hendra; M. Arief Hakim (Jurnal POLIMESIN, 2017)
The background of the palette bolster printer machine production is the availability of waste sawdust in the large number. Waste sawdust is often regarded as a waste that its values and benefits cannot be felt yet. Sawdust can be used as the primary material for the production of palette bolster, so it becomes  valuable and useful. The method used in the machine production are reviewing literature and by doing calculations. The next stage is the production of machines and testing process to find out the success of the design. After the production process, it is obtained the machine results with dimensions of 380×150×510 (mm), with the production capacity of 2 products in one-time process. A good mixture composition of the sawdust and adhesive is 60:40 with a production capacity of 12 per hour, the machine is expected to provide benefits in the palette production. Key words: Adhesive, bolster, pallet, sawdust.